Znaczenie analizy finansowej w procesie decyzyjnym inwestora giełdowego na przykładzie analizy wyników finansowych spółki LPP S.A. - Stojda, Magdalena (My University, 2015)
Niniejsza praca magisterska została poświęcona tematyce oceny sytuacji finansowej spółki akcyjnej, jako źródła informacji dla potencjalnych inwestorów zewnętrznych. Część teoretyczna pracy opiera się na literaturze przedmiotu z zakresu finansów oraz inwestycji. Praktyczną część pracy stanowi analiza danych finansowych spółki giełdowej. Metodą badawczą wykorzystaną w niniejszej pracy było studium przypadku, oparte o wyniki finansowe spółki akcyjnej LPP w latach 2010-2014. W części empirycznej pracy przedstawiono liczne analizy finansowe, w tym analizę bilansu, rachunku zysków i strat, rachunku przepływu środków pieniężnych, a także analizę wskaźnikową oraz analizę wskaźników giełdowych. Wyniki każdej z wymienionych analiz prezentują zmiany w sytuacji finansowej spółki na przestrzeni lat 2010-2014. Na podstawie wyników analiz przedstawiono ocenę prowadzonej polityki zarządczej oraz podejmowanych przez spółkę decyzji strategicznych i finansowych. Wyniki przeprowadzonych analiz danych finansowych spółki LPP w okresie lat 2010-2014 pozwoliły na pozytywne zweryfikowanie 4 z 5 postawionych w niniejszej pracy hipotez badawczych. Co więcej, w pracy udowodniono jak ważna w procesie inwestycyjnym jest rola analizy finansowej spółki giełdowej.

This thesis was devoted to the assessment of the financial situation of a limited company, as a source of information for potential external investors. The theoretical part of the work is based on the literature on finance and investments. The practical part of the work is the analysis of financial data of a listed company. The research method used in the present study was a case study based on the financial results of LPP stock company in 2010-2014. In the empirical part of the study presents numerous financial analysis, including the analysis of the balance sheet, income statement, cash flow statement, as well as ratio analysis and analysis of stock exchange indexes. The results of each of these analyzes represent changes in the financial position of the company in2010-2014. Based on the results of analyzes were presented an assessment of the policy management and undertaken by the company's strategic and financial decisions. The results of the analysis of the financial data of LPP in the period 2010-2014 led to positive verification 4 of 5 posed in this study hypotheses. Pay special attention to the fact that the financial analysis should be accompanied refer to the non-financial situation of the company, on the implemented strategy, investment plans, etc. General knowledge about the company allows better its evaluation, often explaining achieved financial results. In the case of LPP intensive expansion into Western markets has contributed to the reduction in the value of several indicators. However, you can expect to see significant improvement in their connection with the activities of investment. What's more, the work proved how important in the investment process is the role of financial analysis of listed companies.
The importance of financial analysis in stock market investor decision-making process: analysis of the financial results of the LPP SA company
Keywords: LPP S.A.; analiza finansowa; giełda; inwestycje; spółka giełdowa; LPP SA; financial analysis; investment; stock market; stock market company